2022
DOI: 10.3390/jcm11040958
|View full text |Cite
|
Sign up to set email alerts
|

Goal Attainment in an Individually Tailored and Home-Based Intervention in the Chronic Phase after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a heterogeneous condition with long-term consequences for individuals and families. Goal-oriented rehabilitation is often applied, but there is scarce knowledge regarding types of goals and goal attainment. This study describes goal attainment in persons in the chronic phase of TBI who have received an individualized, SMART goal-oriented and home-based intervention, compares goal attainment in different functional domains, and examines indicators of goal attainment. Goal attainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
1
0
2
Order By: Relevance
“…There were no sex/gender differences in either type of goal set or in their attainment in each ICF category. This is inconsistent with some previous research into TBI in which women demonstrated significantly higher goal attainment ( 39 ). However this previous study evaluated a home-based intervention, and most goals were attained, at odds with the post-acute setting and lower rates of attainment seen in the current cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…There were no sex/gender differences in either type of goal set or in their attainment in each ICF category. This is inconsistent with some previous research into TBI in which women demonstrated significantly higher goal attainment ( 39 ). However this previous study evaluated a home-based intervention, and most goals were attained, at odds with the post-acute setting and lower rates of attainment seen in the current cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, 47% of the rehabilitation cohort achieved their goals at the expected level or greater at discharge, which was significantly lower than the overall control cohort (60%), but comparable to TAP (44%). Our goal attainment rate is also higher than reported for a German post-acute inpatient rehabilitation program (31%) ( 32 ) but lower than a Norwegian home-based rehabilitation program for TBI (93%) ( 33 ). GAS scoring guidelines indicate that a goal attainment rate around 50% (or mean score of 50) is expected in large clinical populations ( 17 ), with significantly higher attainment rates suggesting that the initial goals set were too easy.…”
Section: Discussioncontrasting
confidence: 74%
“…The fact that the intervention group showed within-group improvements over time on all outcome measures except the PART-O social subscale supports this interpretation. High goal attainment has been previously documented in this trial, indicating positive intervention effects at an individual level. In a future trial, it would be of interest to include measures of self-efficacy because increased self-efficacy has been proposed to be a primary factor in transfer effects of rehabilitation interventions .…”
Section: Discussionsupporting
confidence: 70%